Pemberdayaan Masyarakat Desa Bunut Baok Kabupaten Lombok Tengah Melalui Pengolahan Limbah Lokal Menjadi Pupuk Organik - Siti Nurhidayati; Khaeruman Khaeruman (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
Bunut Baok Village is one of the villages located in Praya District, Central Lombok Regency. The majority of the people are breeders and farmers. Farmers leave behind mountains of cow manure, have a pungent odor, and pollute the surrounding waters, so that people feel disturbed. Meanwhile, farmers currently have difficulty obtaining fertilizer and the price is very expensive, because chemical fertilizers can boost agricultural/plantation yields. Communities generally use chemical fertilizers, where the excessive use of chemical fertilizers has an impact on environmental damage. For this reason, the community needs to be given knowledge about the processing and benefits of organic fertilizer packaged through community empowerment activities in the form of training and counseling so that they are able to process local waste into organic fertilizer that is environmentally friendly. Through this activity, it is hoped that the community will be able to take advantage of existing local potential and be able to carry out further innovations regarding organic fertilizers, even being able to be packaged and produced in large quantities to be used as a livelihood for the local community. This service activity is carried out in three stages, namely: 1) preparation, in the form of observations and interviews as well as identification of local waste as the main ingredient for making organic fertilizer; 2) outreach to the public about the importance of treating waste so that the environment is kept clean; and 3) training on processing local waste into organic fertilizer. The community is very motivated by this activity, especially because environmental pollution is reduced by waste treatment and can overcome the scarcity of fertilizer they really need.